In-home Drug Storage and Self-medication with Antimicrobial Drugs in Basrah, Iraq - Abdul-Mohsin Jassim (Oman Medical Journal, 2010)
Objectives: To estimate the prevalence of self-medication with antimicrobial drugs and to record the stored medicine at home.Methods: This is a descriptive study involving a questionnaire survey to determine the extent of drug storage and self-medication. A total of 300 household units in Basrah, Iraq were including in this study. A survey was conducted in 300 households in Basrah, southern Iraq to determine the availability, source, and storage conditions of medicinal drugs and the prevalence of self medication with antimicrobials.Results: The majority of households (94%) stored drugs at home. A total of 4279 of different types of drug preparations were encountered, the mean being 14.26 products/household. The results also showed that a minority of these drugs (31%) were rationally prescribed. Hence only 31% of the total drugs were for current use, while 45% were leftovers and 23% of the drugs were kept for future use.A large proportion of the stored drugs (66%) was obtained from private pharmacies. Only 42% of all the drugs were stored appropriately. Antibiotics, as a group was the most common drug stored and used at home (26%). The results indicated that the level of education has influence over dose compliance, storage of expired drugs and drugs exchange.Furthermore, a majority of the families (78%) admitted to practicing self-medication. The most common reasons for self-medication with antimicrobial drugs were associated with influenza, upper respiratory tract infections, diarrhea and tonsillitis.Conclusion: There are numerous indications of inappropriate storage, self- medication, poor compliance and use of drugs that have been kept beyond their expiry date in Basrah, Iraq.